2020
DOI: 10.1038/s41387-020-00131-2
|View full text |Cite|
|
Sign up to set email alerts
|

C-Peptide and leptin system in dichorionic, small and appropriate for gestational age twins—possible link to metabolic programming?

Abstract: Children born small for gestational age (SGA) are at increased risk of future glucose intolerance and type 2 diabetes, possibly after due intrauterine metabolic programming. Soluble leptin receptor (SLR) limits leptin access to signaltransducing membrane receptors. The present study examines whether SGA and appropriate for gestational age (AGA) twins differ with regard to their C-peptide, glucose and leptin systems. The markers C-peptide, glucose, fetal leptin, and SLR in cord blood were assessed in children f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…However, we did not find a difference in cord blood leptin concentration between sIUGR cotwins, which is in conflict with previous studies that reported lower cord blood leptin in SGA neonates in singleton neonates 30–32 but in accordance with the results presented by a similar discordant twin study 26,33 . Interestingly, we found that the cord blood leptin concentration was lower in sIUGR twin pairs than in NC twin pairs, signifying a reduction in leptin levels also found in appropriately grown neonates from sIUGR pregnancies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we did not find a difference in cord blood leptin concentration between sIUGR cotwins, which is in conflict with previous studies that reported lower cord blood leptin in SGA neonates in singleton neonates 30–32 but in accordance with the results presented by a similar discordant twin study 26,33 . Interestingly, we found that the cord blood leptin concentration was lower in sIUGR twin pairs than in NC twin pairs, signifying a reduction in leptin levels also found in appropriately grown neonates from sIUGR pregnancies.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study of weight discordant twins, it has been shown that growth-retarded twins demonstrate insulin resistance with decreased fetal and increased placental leptin levels as compared with co-twins exhibiting appropriate fetal growth. Concomitantly, soluble leptin receptor levels increased in growth-restricted twins limiting leptin access to the membranebound receptor, and thus further enhancing leptin resistance [223]. Fetal leptin derives from the placenta with a less significant contribution in the fetal adipose tissue.…”
Section: Leptinmentioning
confidence: 99%
“…However, leptin is a large protein molecule that cannot pass through the placental barrier, so it is independent of the maternal blood LEP and forms a separate regulatory mechanism. The placental leptin levels in the one twin with small for gestational age (SGA) were significantly higher in comparison with the other normal weight twin of a dichorionic twin pregnancy [ 37 ]. This also suggests that leptin regulation in placenta is independent in the same maternal blood environment.…”
Section: Adipokinementioning
confidence: 99%